2012
DOI: 10.1021/ml3000512
|View full text |Cite
|
Sign up to set email alerts
|

Intestinally Targeted Diacylglycerol Acyltransferase 1 (DGAT1) Inhibitors Robustly Suppress Postprandial Triglycerides

Abstract: High DGAT1 expression levels in the small intestine highlight the critical role this enzyme plays in nutrient absorption. Identification of inhibitors which predominantly inhibit DGAT1 in the gut is an attractive drug discovery strategy with anticipated benefits of reduced systemic toxicity. In this report we describe our discovery and optimization of DGAT1 inhibitors whose plasma exposure is minimized by the action of transporters, including the P-glycoprotein transporter. The impact of this unique absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
(33 reference statements)
0
22
0
Order By: Relevance
“…Intestinal DGAT1 is positioned at a site that makes it a good candidate for impacting the postprandial TG response. Pharmacological inhibitors of DGAT1 have been shown to effectively reduce the postprandial TG response to an HFM challenge [ 36 , 37 , 40 , 41 ], but not without significant and intolerable gastrointestinal side effects in humans like nausea, diarrhea and vomiting. This indicates that intestinal DGAT1 is a good target to reduce postprandial TG levels.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal DGAT1 is positioned at a site that makes it a good candidate for impacting the postprandial TG response. Pharmacological inhibitors of DGAT1 have been shown to effectively reduce the postprandial TG response to an HFM challenge [ 36 , 37 , 40 , 41 ], but not without significant and intolerable gastrointestinal side effects in humans like nausea, diarrhea and vomiting. This indicates that intestinal DGAT1 is a good target to reduce postprandial TG levels.…”
Section: Discussionmentioning
confidence: 99%
“…[147] Serrano-Wu of Novartis presented 37,w hich is an anomolar inhibitor of DGAT1 and has been characterizedi nr ats and in dogs. [148] Pradigastat( 38,f ormerlyL CQ-908) has been tested in healthy human subjects, in which it suppressed postprandial TGs in ad ose-dependentmanner,w ith maximum suppression of % 90 %, [149] and provede ffective in patients with familialc hylomicronemia syndrome (FCS). [150] Although 38 is the clinically most advanced compound, no IC 50 and selectivity data have so far been published, and this makesi ts use as at ool compound problematic.T wo new compounds that have not yet enteredc linical trials but exhibit very high activity against DGAT1 have recently been reported:M erck presented inhibitor 39,w hich has been profiled against ap anel of more than 100 other targets,i nw hich it showed > 10 mm against all protein targets with the exception of A2A receptor (K i = 4.6 mm), which makes it the best-characterized tool compound for DGAT1.…”
Section: Diacylglycerol Acyltransferases (Dgats)mentioning
confidence: 99%
“…of Astra–Zeneca introduced the reversible arylpyrazine‐based inhibitor AZD7687 ( 36 ), which showed 400× selectivity towards DGAT1 versus acyl‐coenzyme A:cholesterol acyltransferase 1 (ACAT1), and was entered into Phase I clinical trials, in which it showed the expected reduction of triglycerides in plasma, but intolerable side effects in the form of severe diarrhea . Serrano‐Wu of Novartis presented 37 , which is a nanomolar inhibitor of DGAT1 and has been characterized in rats and in dogs . Pradigastat ( 38 , formerly LCQ‐908) has been tested in healthy human subjects, in which it suppressed postprandial TGs in a dose‐dependent manner, with maximum suppression of ≈90 %, and proved effective in patients with familial chylomicronemia syndrome (FCS) .…”
Section: Acyltransferasesmentioning
confidence: 99%
“…To investigate PK and PD correlation, we examined intestinal disposition of 43c. DGAT1 is mainly expressed in intestine [18]. Whole mouse small intestine was collected to estimate the total intestinal concentration of 43c could represent total amount in the intestinal area including lumen.…”
Section: Figmentioning
confidence: 99%